Contextualizing mistreatment in cognitive impairment in Latin America. Issue 3 (27th May 2019) - Piña-Escudero, Stefanie Danielle; Weinstein, Cindy A.; Ritchie, Christine
ABSTRACT: Mistreatment is an important social outcome of the growing cognitive impairment epidemic, particularly in developing countries. This study aimed to bring to light what is known about mistreatment in cognitively impaired individuals in Latin American Countries. We identified a gap in the literature on this topic that opens the door for future research.